2015
DOI: 10.1007/s40878-015-0003-x
|View full text |Cite
|
Sign up to set email alerts
|

Trade unions, immigration and immigrants in Europe revisited: Unions’ attitudes and actions under new conditions

Abstract: This paper revisits the comparative approach used by Penninx and Roosblad (Trade Unions, Immigration and Immigrants in Europe, 1960-1993. New York: Berghahn Books) to study trade unions' attitudes and actions in relation to immigrant workers in seven Western European countries. It reassesses that approach and asks whether it remains valid, as economic, social, and political circumstances nowadays seem fundamentally different from those two to five decades ago. Each element of the original conceptual and explan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
63
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 41 publications
5
63
0
5
Order By: Relevance
“…Several studies suggest that this is not only explained by the individual characteristics of migrants, such as the overrepresentation of migrants in particular industries or occupations that are less organized, but also by contextual factors that affect how inclusive trade unions are towards migrant workers (e.g. Cachón and Valles 2003;Eldring et al 2012;Gorodzeisky and Richards 2013;Krings 2009;Lucio and Perrett 2009;Marino 2012;Penninx and Roosblad 2000;Wrench 2004). This study connects to this strand of literature by exploring to what extent the difference between the unionization rates of migrants and natives in European countries are explained by contextual factors related to the industrial relations regime of a country, in addition to the individual characteristics of migrants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies suggest that this is not only explained by the individual characteristics of migrants, such as the overrepresentation of migrants in particular industries or occupations that are less organized, but also by contextual factors that affect how inclusive trade unions are towards migrant workers (e.g. Cachón and Valles 2003;Eldring et al 2012;Gorodzeisky and Richards 2013;Krings 2009;Lucio and Perrett 2009;Marino 2012;Penninx and Roosblad 2000;Wrench 2004). This study connects to this strand of literature by exploring to what extent the difference between the unionization rates of migrants and natives in European countries are explained by contextual factors related to the industrial relations regime of a country, in addition to the individual characteristics of migrants.…”
Section: Introductionmentioning
confidence: 99%
“…While most previous studies use qualitative methods to analyse the role of contextual factors (e.g. Cachón and Valles 2003;Eldring et al 2012;Krings 2009;Lucio and Perrett 2009;Marino 2012;Penninx and Roosblad 2000;Wrench 2004), this study applies a quantitative research design. With a multilevel logistic regression analysis we examine to what extent the differences in unionization rates between migrants and natives in 23 European countries are explained by the individual characteristics of the migrants on the one hand and by country characteristics, related to the role of the trade unions and the industrial relations regime, on the other.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the relative success or failure of these shifts in union strategies, the representation gap between native-born and migrant workers persists, and a long-standing debate exists as to why this should be so. Some authors have focused on the behaviour and incentives of unions themselves (Marino et al 2015;Penninx and Roosblad 2002;Quinlan and Lever-Tracy 1990). For example, in his study of trade union policies and actions towards minority workers in Italy and the Netherlands, Marino (2012) found an inverse relationship between unions' institutional embeddedness and their perception of migrant workers as a 'power resource'.…”
Section: Unions and Migrantsmentioning
confidence: 99%
“…Some authors have focused on the behaviour and incentives of unions themselves (Marino et al 2015;Penninx and Roosblad 2002;Quinlan and Lever-Tracy 1990). For example, in his study of trade union policies and actions towards minority workers in Italy and the Netherlands, Marino (2012) found an inverse relationship between unions' institutional embeddedness and their perception of migrant workers as a 'power resource'. In a very similar vein, Gorodzeisky and Richards (2013) showed that the institutional position of unions affects migrant workers' unionization rates relative to those of local workers.…”
Section: Unions and Migrantsmentioning
confidence: 99%
See 1 more Smart Citation